2019
DOI: 10.1097/mpg.0000000000002273
|View full text |Cite
|
Sign up to set email alerts
|

Biliary Tract Disease in Girls and Young Women With Rett Syndrome

Abstract: Objective: We reviewed medical records and conducted a nationwide survey to characterize the clinical features and determine the prevalence of biliary tract disease in girls and women with Rett syndrome (RTT). Methods: Sixty-two individuals with RTT and biliary tract disease were identified from the membership of Rett Syndrome Organization (RS.O) and patient files of the principal investigator. Medical records of 46 individuals were reviewed for presenting features, diagnostic tests, and treatment outcomes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…23 The majority of cross-sectional studies (5 articles) also involved data collection through in person assessments; 2 studies that were multisite 24 25 and 3 that were single institution. [26][27][28] Of the remaining cross-sectional studies (4 articles), three involved data collection through remotely disseminated caregiver completed questionnaires [29][30][31] and a single study involved retrospective medical records review. 32 The multisystem nature of the disorder is quite apparent based on the observational studies identified in this scoping review (table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 The majority of cross-sectional studies (5 articles) also involved data collection through in person assessments; 2 studies that were multisite 24 25 and 3 that were single institution. [26][27][28] Of the remaining cross-sectional studies (4 articles), three involved data collection through remotely disseminated caregiver completed questionnaires [29][30][31] and a single study involved retrospective medical records review. 32 The multisystem nature of the disorder is quite apparent based on the observational studies identified in this scoping review (table 2).…”
Section: Resultsmentioning
confidence: 99%
“…33 Biliary tract disease does not appear to impact individuals with RTT at a higher rate (4%) than the general population but may be difficult to recognise due to non-specific symptoms overlapping with behaviour disturbances and the underlying communication impairments in RTT. 30 Scoliosis is the most frequently encountered orthopaedic issue with 85% of individuals 16 years or older diagnosed with this finding. Its occurrence is age-dependent though with much lower prevalence in childhood and increasing prevalence through adolescence.…”
Section: Resultsmentioning
confidence: 99%
“…In a cohort of 983 females with RTT, 81% had feeding problems (principally chewing difficulty, prolonged feeding time, and choking), 92% had GI problems (gastroesophageal reflux, constipation, straining with bowel movements, and passage of hard stools), and 47% had nutritional problems (poor weight principally) 24 . A small percentage (4.4%) of patients also have biliary tract disease, which may have a fatal outcome 25 .…”
Section: Digestive Systemmentioning
confidence: 99%
“…Although neurological symptoms predominate, more than 90% of girls with RTT develop gastrointestinal problems that affect their health and quality of life [4][5][6][7] and pose a substantial medical challenge for their caregivers [4,8]. Chewing and swallowing dysfunction, gastroesophageal reflux, gastroparesis, biliary tract disorders, gas bloating, and constipation complicate the clinical course of this disorder [4,5]. Disturbances in gastrointestinal function predispose girls with RTT to individual nutrient deficits, protein-energy malnutrition, and growth failure [4,6,7].…”
Section: Introductionmentioning
confidence: 99%